PENGARUH MOTIVASI, DISIPLIN KERJA DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOUR TERHADAP KINERJA KARYAWAN PADA DISTRIK NAVIGASI KELAS II SEMARANG - Sony Sandi Yudha, 14.05.51.0073; Rahayuningsih, Sri (Students' Journal of Economic and Management, 2018)
This study aims to examine and analyze the influence of Motivation, Work Discipline and Organizational Citizenship Behavior on Employee Performance. The object of research in this writing is the Class II Navigation District of Semarang. The sampling technique in this study was using purposive sampling technique with the number of respondents 116 people. The data analysis tool used in this research is the Multiple Linear Regression Analysis, where previously Validity and Reliability were tested. The results of the research are: (1) Motivation has a positive and significant effect on employee performance, the higher the motivation in the employee, the employee's performance is also increasing. (2) Work Discipline has a positive and significant effect on employee performance, the higher the Work Discipline in the employee, the employee's performance also increases. (3) Organizational Citizenship Behavior has a positive and significant effect on employee performance, the higher the Organizational Citizenship Behavior in employees, the employee's performance is also increasing. Keywords : Motivation, Work Discipline, and Organizational Citizenship Behavior and Employee Performance